COMPACTION-DRIVEN FLUID FLOW IN VISCOELASTIC ROCK - Connolly J.A.D.; Podladchikov Y.Y. (My University, 1998)
Compaction driven fluid flow is inherently unstable such that an obstruction to upward fluid flow (i.e. a shock) may induce fluid-filled waves of porosity, propagated by dilational deformation due to an effective pressure gradient within the wave. Viscous porosity waves have attracted attention as a mechanism for melt transport, but are also a mechanism for both the transport and trapping of fluids released by diagenetic and metamorphic reactions. We introduce a mathematical formulation applicable to compaction driven flow for the entire range of rheological behaviors realized in the lithosphere. We then examine three first-order factors that influence the character of fluid flow: (1) thermally activated creep, (2) dependence of bulk viscosity on porosity, and (3) fluid flow in the limit of zero initial connected porosity. For normal geothermal gradients, thermally activated creep stabilizes horizontal waves, a geometry that was thought to be unstable on the basis of constant viscosity models. Implications of this stabilization are that: (1) the vertical length scale for compaction driven flow is generally constrained by the activation energy for viscous deformation rather than the viscous compaction length, and (2) lateral fluid flow in viscous regimes may occur on greater length scales than anticipated from earlier estimates of compaction length scales. In viscous rock, inverted geothermal gradients stabilize vertically elongated waves or vertical channels. Decreasing temperature toward the earth's surface can induce an abrupt transition from viscous to elastic deformation-propagated fluid flow. Below the transition, fluid flow is accomplished by short wavelength, large amplitude waves; above the transition flow is by high velocity, low amplitude surges. The resulting transient flow patterns vary strongly in space and time. Solitary porosity waves may nucleate in viscous, viscoplastic, and viscoelastic rheologies. The amplitude of these waves is effectively unlimited for physically realistic models with dependence of bulk viscosity on porosity. In the limit of zero initial connected porosity, arguably the only model relevant for melt extraction, travelling waves are only possible in a viscoelastic matrix. Such waves are truly self-propagating in that the fluid and the wave phase velocities are identical; thus, if no chemical processes occur during propagation, the waves have the capacity to transmit geochemical signatures indefinitely. In addition to solitary waves, we find that periodic solutions to the compaction equations are common though previously unrecognized. The transition between the solutions depends on the pore volume carried by the wave and the Darcyian velocity of the background fluid flux. Periodic solutions are possible for all velocities, whereas solitary solutions require large volumes and low velocities.